2007
DOI: 10.1111/j.1939-165x.2007.tb00201.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of platelet parameters in EDTA‐ and citrate‐anticoagulated blood in dogs

Abstract: Platelets aggregate, likely from activation, when blood from dogs with neoplasia is anticoagulated with citrate for hematology testing, resulting in lower platelet counts. Citrate also yields inaccurate results for MPV and MPC, likely because of inadequate sphering of platelets. Thus, we recommend that citrate not be used as an anticoagulant when accurate platelet counts are desired in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 27 publications
8
33
2
Order By: Relevance
“…9,23,29 Despite the fact that the overall frequency of platelet clumping in the present study may have been affected by a relatively low threshold for abnormality (at least 3 aggregates, each consisting of $3 platelets), clumping was significantly more frequent in citrate-compared to EDTA-anticoagulated blood and was more pronounced at lower temperatures. As is the case with cats, the prolonged storage of blood (up to 24 hr postsampling) does not appear to substantially accentuate this phenomenon in dogs.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…9,23,29 Despite the fact that the overall frequency of platelet clumping in the present study may have been affected by a relatively low threshold for abnormality (at least 3 aggregates, each consisting of $3 platelets), clumping was significantly more frequent in citrate-compared to EDTA-anticoagulated blood and was more pronounced at lower temperatures. As is the case with cats, the prolonged storage of blood (up to 24 hr postsampling) does not appear to substantially accentuate this phenomenon in dogs.…”
Section: Discussionmentioning
confidence: 63%
“…6,7,28,31 In a 1986 study, 6 the maximum MPV was observed in EDTA-anticoagulated canine blood stored at 4uC, while minimum MPV alteration was observed in citrate-anticoagulated blood stored at 37uC. Interestingly, in a study published in 1989, 34 no EDTA-or storage temperature-mediated impact was demonstrated on the MPV of healthy dogs determined over a period of 30 hr postsampling in an impedance analyzer, while a 2007 study 29 demonstrated a significant increase of MPV in citrate-anticoagulated compared to EDTA-anticoagulated canine blood processed in an optical analyzer within an hour of collection. This discrepancy may be partially explained by the different study design (instrumentation, different blood sampling timing, number of dogs, consideration of macroplatelet percentages instead of MPV, concentration of EDTA, and different degrees of platelet activation or aggregation).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations